Financial wellbeing: mapping the determining factors - Silva, Nathállya Etyenne Figueira; Callado, Aldo Leonardo Cunha; Silva, Yuri Laio Teixeira Veras (Brazilian Journal of Production Engineering, 2024)
Financial well-being has become an important element for individuals and families, as well as for governments and institutions, due to record-high savings rates and inadequate long-term financial planning. Understanding what is associated with financial well-being and how to improve it becomes an important goal. Therefore, this article aims to conduct a systematic review of the literature, seeking to identify factors that influence/determine financial well-being. To this end, the steps proposed by Donato and Donato (2019) were followed. Forty articles were selected from the Web of Science (WoS), Scopus, SciELO and Spell databases for the analysis. The results pointed to important relationships between financial well-being and elements representing financial literacy, specifically financial behaviors. In addition, financial inclusion, financial socialization, financial capability, self-efficacy and happiness are also considered determining factors.
Keywords: Financial well-being; Systematic review; Financial literacy; Financial behavior